Deciphering the Genetic Basis of Lodging Resistance in Wild Rice Oryza longistaminata - Long, Weixiong; Dan, Dong; Yuan, Zhengqing; Chen, Yunping; Jin, Jie; Yang, Weilong; Zhang, Zhihong; Li, Nengwu; Li, Shaoqing (Frontiers in Plant Science, 2020)
The abuse of fertilizer results in tall rice plants that are susceptible to lodging and reduced plant yield. Hence, it is important to identify and utilize the QTLs/genes for lodging resistance breeding. O. longistaminata exhibited a strong stem and high biomass productively, which could be the candidate gene pool for cultivars lodging resistance improvement. However, most of previous studies have focused on cultivated rice and few reports on wild rice. Here, a set of 152 BC2F20 lines derived from a cross between 93-11 and O. longistaminata were evaluated for lodging resistance. QTL mapping analysis combined with SNP marker derived from high-throughput sequencing identified 12 QTLs for stem diameter (SD), 11 QTLs for stem length (SL) and 3 QTLs for breaking strength (BS). Of which, 14 QTLs were firstly identified from O. longistaminata. A major QTL, qLR1 which was delimited to a region about 80 Kb on chromosome 1, increased stem diameter, stem length and breaking strength. And another major QTL, qLR8 that was delimited in an interval about 120 Kb on chromosome 8, significantly enhanced the breaking strength. These results provide evidence that the O. longistaminata can be exploited to develop lodging resistant rice lines.